Diversity of bacterial communities in traditional sourdough derived from three terrain conditions (mountain, plain and basin) in Henan Province, China. (July 2020) - Xing, Xiaolong; Ma, Jingyi; Fu, Zhongjun; Zhao, Yirui; Ai, Zhilu; Suo, Biao
Graphical abstract: Highlights: The bacterial communities of sourdoughs from three terrain conditions were analysed. The three dominant genera in the sourdoughs were Pediococcus, Lactobacillus, and Acetobacter. Terrain conditions (mountain, basin and plain) influenced bacterial diversity. Abstract: To elucidate the bacterial community composition of sourdoughs from different terrain conditions, thirty-two Chinese traditional sourdough samples were collected from three terrain conditions (mountain, plain and basin) in Henan Province. High-throughput sequencing and culture-dependent approaches were employed to identify the bacterial diversity of the sourdough samples. A total of two hundred and six isolates were characterized via 16S rRNA gene sequencing. Pediococcus pentosaceus was isolated from every sample and was the predominant species in the sourdough samples, accounting for 58% of the relative abundance. High-throughput sequencing revealed that the predominant genera (mainly Pediococcus) in the basin group were significantly different from those in the mountain and plain groups. The genus Lactobacillus was predominant in the plain and mountain sourdough samples. Pediococcus pentosaceus was the absolute dominant strain in the basin sourdough samples. Acetobacter, which was widely distributed only in mountain samples, was recognized as the representative genus of the mountain samples. Moreover, we first reported Gluconobacter oxydans in sourdough. This study provided insight into the bacterial diversity of sourdough from three terrain conditions (mountain, plain and basin) in Henan Province and could serve as a reference for the isolation of desired bacterial strains.